INTANGIBLE ASSETS: MOVEMENT, REPRODUCTION AND USE OF EFFICIENCY - Dobrovolska , E. V.; Korzhenivska, N. L.; Koval, N. V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
In the process of historical development of the productive forces there were changes in their composition and structure. Leading positions among other types of resources were occupied by material and raw materials, material and technical, financial and labor. Recently, the intangible components of the enterprise have become increasingly important in the composition of resources. Thanks to the latest technologies, commercial designations, human capital, goodwill and other intangible components, companies are able to gain an advantage in competition. In the world's leading economies, the intangible resources of enterprises have already exceeded their material values. The methodological basis of the study is the induction and deduction methods, analysis and synthesis, scientific knowledge, system analysis for structuring intangible resources and indicators of their efficiency; factual analysis to determine the problems of development of enterprises of Khmelnytsky region and LLC "Tsukoragroprom"; economic and statistical methods for calculating the efficiency of intangible resources of enterprises; expert assessments and multidimensional statistical analysis methods to determine the level of development of intangible resources of enterprises. The study focuses on assessing the level of development of intangible resources, which provides an opportunity to identify the most effective ways to increase the level of development of intangible resources and the efficiency of their use; the main tendencies of movement, reproduction and efficiency of use of intangible resources are considered. The result of the study is to ensure the process of choosing the most effective ways to increase the level of development of intangible assets of the enterprise.